A new model for global glacier change and sea-level rise - Huss, Matthias; Hock, Regine (Frontiers in Earth Science, 2015)
The anticipated retreat of glaciers around the globe will pose far-reaching challenges to the management of fresh water resources and significantly contribute to sea-level rise within the coming decades. Here, we present a new model for calculating the twenty-first century mass changes of all glaciers on Earth outside the ice sheets. The Global Glacier Evolution Model (GloGEM) includes mass loss due to frontal ablation at marine-terminating glacier fronts and accounts for glacier advance/retreat and surface elevation changes. Simulations are driven with monthly near-surface air temperature and precipitation from 14 Global Circulation Models forced by RCP2.6, RCP4.5, and RCP8.5 emission scenarios. Depending on the scenario, the model yields a global glacier volume loss of 25–48% between 2010 and 2100. For calculating glacier contribution to sea-level rise, we account for ice located below sea-level presently displacing ocean water. This effect reduces the glacier contribution by 11–14%, so that our model predicts a sea-level equivalent (multi-model mean ±1 standard deviation) of 79±24 mm (RCP2.6), 108±28 mm (RCP4.5), and 157±31 mm (RCP8.5). Mass losses by frontal ablation account for 10% of total ablation globally, and up to 30% regionally. Regional equilibrium line altitudes are projected to rise by 100–800 m until 2100, but the effect on ice wastage depends on initial glacier hypsometries.